PENCIPTAAN ILUSTRASI BUKU “WAYANG BEBER WONOSARI” - Indiria Maharsi (Institut Seni Indonesia Yogyakarta, 2018)
Abstract.Wayang Beber Wonosari is one of the cultural heritages created by the ancestors of Indonesians. It has exsisted for so long time, but many people have not known it yet. In the effort to preserve it, it is urgent to informed people about it, especially its latest development. To invite their attention to this content, illustration book can be effectively used to deliver the information.Keywords:Wayang Beber Wonosari,illustration book.